Baitul Mal Aceh and Productive Zakat Education for Mustahiq - Muhammad Ichsan Sukmawati (Bulletin of Islamic Research, 2024)
There are eight groups of zakat recipients mentioned in the Koran. Without Baitul Mal Aceh's maximum role, especially in distributing productive Zakat, what the mustahiq receive may not be used productively. Zakat education is one of the things that can be done so that zakat recipients can really understand and make good use of the assistance. Therefore, Baitul Mal Aceh in particular has a very strategic role so that the zakat funds distributed to mustahiq, especially productive zakat, can really be utilized optimally and it is even hoped that the recipients will become muzakki in the future. Zakat education for mustahiq needs to continue to receive attention, including in terms of evaluating the provision of zakat. Religious education has an important role in providing understanding and awareness so that Muslims, especially mustahiq, become people who do not waste the wealth they have. The forms of education that can be given to them include: teaching knowledge about zakat, awakening their hearts with the light of faith, providing an understanding of zakat, and instilling in their hearts that using wealth well is part of worship.